Ground‐based InSAR reveals conduit pressurization pulses at Stromboli volcano. (31st December 2012) - Di, Federico; Del, Chiara; Rosi, Mauro; Mugnai, Francesco; Intrieri, Emanuele; Moretti, Sandro; Casagli, Nicola
Abstract At Stromboli volcano (Southern Italy), only few minor precursors (gas output) have been identified for 'major' Strombolian explosions. We use ground‐based interferometric synthetic aperture radar (GBInSAR) technology to monitor the displacement rate of the summit area of Stromboli. We analysed the 2009–2011 period. The analysis of the displacement rate has been performed by dividing the summit zone monitored by the GBInSAR into three regions, corresponding to the edge of the crater area (1 and 2), and to the slope of the NE crater (3). Pulses of rapid expansion of sector 3, of variable duration and amplitude, appear in coincidence with periods of intense activity that include lava flows and major explosions. We associate this expansion with the pressurization of the magma column that is recharged by deep‐derived gas, promoting the onset of 'major explosion‐dominated' activity.